2013
DOI: 10.1002/ar.22695
|View full text |Cite
|
Sign up to set email alerts
|

Airway Morphology From High Resolution Computed Tomography in Healthy Subjects and Patients With Moderate Persistent Asthma

Abstract: Models of the human respiratory tract developed in the past were based on measurements made on human tracheobronchial airways of healthy subjects. With the exception of a few morphometric characteristics such as the bronchial wall thickness (WT), very little has been published concerning the effects of disease on the tree structure and geometrical features. In this study, a commercial software package was used to segment the airway tree of seven healthy and six moderately persistent asthmatic patients from hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Although 3D acquisition together with automatic analysis is time saving and is widely accepted as an optimal standard, in the study of airway morphometric characteristics in patients with asthma, the main structural features were reported to be identical with those found in HRCT alone, including bronchial wall thickness and emphysema (21)(22)(23). Furthermore, 3D is more likely to be regarded as a post-processing method, because changes visualized in twodimension (2D) projections were demonstrated to correspond to the airway flow limitations well (24).…”
Section: Introductionmentioning
confidence: 99%
“…Although 3D acquisition together with automatic analysis is time saving and is widely accepted as an optimal standard, in the study of airway morphometric characteristics in patients with asthma, the main structural features were reported to be identical with those found in HRCT alone, including bronchial wall thickness and emphysema (21)(22)(23). Furthermore, 3D is more likely to be regarded as a post-processing method, because changes visualized in twodimension (2D) projections were demonstrated to correspond to the airway flow limitations well (24).…”
Section: Introductionmentioning
confidence: 99%
“…Some pathologies affect the tree structure; in asthma for instance, airways can be constricted. This goes from frequent moderate constrictions throughout the tree with airway radii reductions of 10 to 25% on average [18], [2] up to, in a low proportion of cases, complete closure [10], [8]. These latter severe constrictions will be designated as plugs.…”
Section: Global Methodologymentioning
confidence: 99%
“…Another clinical application of the airway obstruction distribution could be to predict aerosol deposition, which can be greatly affected by bronchoconstrictions [6]. High resolution computed tomography (HRCT) can show the presence of constrictions in asthmatic patients [7], [8] but only proximal airways are easily accessible with current resolutions. However, given the fact that histological analysis demonstrates that more distal branches can be constricted [9], [10], greater resolution is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation can induce airway constrictions (Montaudon et al, 2009) (Kotaru et al, 1985) up to closure (Montesantos et al, 2013) (Aikawa et al, 1992). While some studies argue these pathologies mostly occur in small airways (Burgel, 2011) (Carr et al, 1998), autopsies on patients who died from status asthmaticus (Dunnill, 1960) (Aikawa et al, 1992) and CT scans of diseased subjects have shown upper airways can also be affected (Montesantos et al, 2013).…”
Section: Modeling Disease Of the Tracheo-bronchial Treementioning
confidence: 99%
“…In addition to those small constrictions, (Carr et al, 1998) demonstrates the presence of airway closures in asthmatic patients. In (Montesantos et al, 2013) segmented images of asthmatic patients indicate that severe stenoses can completely occlude airways. Non-published data from this study give the number of closures per segmented tree.…”
Section: Modeling Disease Of the Tracheo-bronchial Treementioning
confidence: 99%